The moral law : groundwork of the metaphysics of morals - Kant, Immanuel (Senior series. [from old catalog], 2005)
Few books have had as great an impact on intellectual history as Kant's The Moral Law. In its short compass one of the greatest minds in the history of philosophy attempts to identify the fundamental principle 'morality' that governs human action.